2019
DOI: 10.1093/nar/gkz589
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the G-rich VEGF-binding aptamer V7t1: when two G-quadruplexes are better than one!

Abstract: The G-quadruplex-forming VEGF-binding aptamer V7t1 was previously found to be highly polymorphic in a K+-containing solution and, to restrict its conformational preferences to a unique, well-defined form, modified nucleotides (LNA and/or UNA) were inserted in its sequence. We here report an in-depth biophysical characterization of V7t1 in a Na+-rich medium, mimicking the extracellular environment in which VEGF targeting should occur, carried out combining several techniques to analyse the conformational behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 59 publications
(68 reference statements)
8
50
0
Order By: Relevance
“…Compared to the Na + -rich medium, completely different was the behavior observed in both gels for V7t1 in TRIS/K + buffer (Figure 1b and Figure S4b), here analyzed for the first time. In addition, in these saline conditions, V7t1 showed the presence of two distinct bands corresponding to the monomeric and dimeric G4 structures found in HEPES/Na + buffer [17], but without detectable differences between the N.A. and A. samples (Figure 1b and Figure S4b, lanes 1 and 2).…”
Section: Gel Electrophoresis Analysismentioning
confidence: 88%
See 3 more Smart Citations
“…Compared to the Na + -rich medium, completely different was the behavior observed in both gels for V7t1 in TRIS/K + buffer (Figure 1b and Figure S4b), here analyzed for the first time. In addition, in these saline conditions, V7t1 showed the presence of two distinct bands corresponding to the monomeric and dimeric G4 structures found in HEPES/Na + buffer [17], but without detectable differences between the N.A. and A. samples (Figure 1b and Figure S4b, lanes 1 and 2).…”
Section: Gel Electrophoresis Analysismentioning
confidence: 88%
“…Overall, no sensible difference in terms of aggregate In both gel assays, in the selected HEPES/Na + buffer, all the investigated V7t1 dimers showed a detectable difference if in N.A. or A. forms, as in the case of V7t1 [17]. In particular, bisV7t1T7 and bisV7t1HEG2 in the N.A.…”
Section: Gel Electrophoresis Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…In the last decade, increased interest has shown in truncating aptamers to variants that show enhanced activity (18,19). In fact, we and others have shown that the truncation and dimerization of aptamers resulted in the enhanced binding properties of molecules against cellular targets (18,20,21).…”
Section: Introductionmentioning
confidence: 99%